Involvement of the insular cortex in the consolidation and expression of contextual fear conditioning - Alves, Fernando H. F.; Gomes, Felipe V.; Reis, Daniel G.; Crestani, Carlos Cesar [UNESP]; Corrêa, Fernando M. A.; Guimarães, Francisco S.; Resstel, Leonardo B. M. (Wiley, 2013)
The insular cortex (IC) has been reported to be involved in the modulation of memory and autonomic and defensive responses. However, there is conflicting evidence about the role of the IC in fear conditioning. To explore the IC involvement in both behavioral and autonomic responses induced by contextual fear conditioning, we evaluated the effects of the reversible inhibition of the IC neurotransmission through bilateral microinjections of the non-selective synapse blocker CoCl2 (1 mm) 10 min before or immediately after the conditioning session or 10 min before re-exposure to the aversive context. In the conditioning session, rats were exposed to a footshock chamber (context) and footshocks were used as the unconditioned stimulus. Forty-eight hours later, the animals were re-exposed to the aversive context for 10 min, but no shock was given. Behavioral (freezing) as well as cardiovascular (arterial pressure and heart rate increases) responses induced by re-exposure to the aversive context were analysed. It was observed that the local IC neurotransmission inhibition attenuated freezing and the mean arterial pressure and heart rate increase of the groups that received the CoCl2 either immediately after conditioning or 10 min before re-exposure to the aversive context, but not when the CoCl2 was injected before the conditioning session. These findings suggest the involvement of the IC in the consolidation and expression of contextual aversive memory. However, the IC does not seem to be essential for the acquisition of memory associated with aversive context. © 2013 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
Keywords: Autonomic system; Blood pressure; Freezing; Heart rate; Prefrontal cortex; Rat; animal behavior; animal experiment; animal tissue; arterial pressure; cardiovascular response; conditioning; contextual fear conditioning; controlled study; discrimination learning; fear; footshock; functional anatomy; heart rate; insula; male; memory consolidation; neuroanatomy; nonhuman; presynaptic inhibition; priority journal; rat; response time; stimulus response